Refractive Error Correction in Bali, Indonesia: A Retrospective Cohort Study of ReLEx SMILE and Femto-LASIK Outcomes - Semara Budiyasa; Indira Putri (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2024)
Introduction: Technological advances have driven progress in surgical techniques for refractive problems, including the use of laser-assisted in situ keratomileusis (LASIK) through the ReLEx SMILE and Femto-LASIK methods. While Bali Mandara Eye Hospital pioneered LASIK procedures in Bali Province, there has been no research to date evaluating the outcomes of these procedures. Methods: This retrospective cohort study analyzed medical record data from patients with refractive disorders who underwent LASIK surgery at Bali Mandara Eye Hospital between January and December 2023. The data collected included patient demographics, pre-and post-operative visual acuity, and the type of LASIK surgery performed. Results: The study included 151 eyes. The majority of patients were male (52.3%), aged 17-29 years, had a college education (60.3%), worked in the private sector (38%), resided in Bali (86%), and underwent the ReLEx SMILE procedure (60.3%). Both Femto-LASIK and ReLEx SMILE procedures yielded excellent visual outcomes and were considered safe. Post-operative uncorrected visual acuity (UCVA) improved to the level of pre-operative best-corrected visual acuity (BCVA) in 137 eyes (90.73%). Conclusion: The ReLEx SMILE and Femto-LASIK methods are both safe and effective procedures for correcting refractive errors, particularly mild myopia. There was no significant difference in visual outcomes between the two methods.